Factors Affecting Commitment in Organizing Behavior - Tubagus Achmad Darodjat (Junal Ilmu Manajemen, 2020)
Strong goals and desires are one of the meanings of commitment. These words are always demanded of individuals who are undergoing a relationship between individuals and agencies or organizations. Commitment is characterized by a form of positive loyalty, active in the work. Where these individuals are willing to give everything in order to realize the goals and continuity of the organization. When we commit ourselves in the heart, then every job carried out becomes lighter. Energy, totality, compactness and confidence to achieve a goal of mutual success will be created by itself. Commitment is a complete acknowledgment, as an attitude that originates in one's character. Commitment is not limited to words but a series of actions to realize a promise becomes a tangible proof, with a commitment we will get courage, high social stability and of course tolerance, so that we are able to survive in facing any difficult situation, because with our commitment is not easily provoked.commitment